Fundamentos microeconomicos de la macroeconomia del crecimiento desbalanceado - Raffo López, Leonardo (Sociedad y Economía, 2006)
This paper intends to reformulate the famous Baumol’s macroeconomics model of unbalanced growth. The inspection of its basic tenets using a new version of the model that includes the demand side of analysis shows that it is unfounded to say that there is a tendency for the outputs of the “nonprogressive” sector to dwindle progressively in time. The solution of the optimum control problem for the model reveals that free market solutions are not Pareto optima. The government intervention is essential to match negative consumption’s externalities created by increasing urbanisation, but also to correct the dynamic inefficiency induced by the unbalanced growth of productivity.